Axial and Flexural Load Test on Untreated Bamboocrete Multi-Purpose Panel - Mohd Daud, Norhasliya; Mohamad Nor, Norazman; Yusof, Mohammed Alias; Yahya, Muhamad Azani; Munikanan, Vikneswaran (International Journal of Integrated Engineering, 2018)
In this study, the axial and flexural strength of lightweight concrete panel reinforced with untreated bamboo describe as bamboocrete multi-purpose panel was investigated. Bamboo is a low cost, abundantly ready available and sustainable material used to carry load.Â  In this research, bamboo is used to reinforce lightweight concrete to form a load bearing panel. From the test conducted, design axial strength of the panel can be up to 100kN (10 ton). The 1500 mm length, 500 mm wide, and 125 mm thick, bamboocrete panel then were subjected to four-point bending and achieved ultimate bending strength of at least 25 kN. The bamboo used in the concrete panel greatly contributed to the bending strength of the panel. Upon removal of the load, the bamboocrete panel return to almost its original form, showing flexibility and ductility of the panel.